1993
DOI: 10.1038/bjc.1993.266
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid infusion blocks renal tubular uptake of an indium-labelled somatostatin analogue

Abstract: Summary The Indium-labelled somatostatin analogue pentetreotide has been successfully developed for imaging of somatostatin receptor positive tumours. However there is significant renal tubular uptake of the radiolabelled peptide, which can obscure upper abdominal tumours and would preclude its use for targeted radiotherapy. The aim of this study was to determine whether amino acid infusion, which has been shown to block renal tubular peptide reabsorption, diminishes renal parenchymal uptake of this radiolabel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(87 citation statements)
references
References 6 publications
3
83
0
1
Order By: Relevance
“…For OCT as a radiolabeled peptide, this effect was demonstrated in the early 1990s (13). It is assumed that uptake of OCT occurs in the proximal tubule cells in the kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…For OCT as a radiolabeled peptide, this effect was demonstrated in the early 1990s (13). It is assumed that uptake of OCT occurs in the proximal tubule cells in the kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…Several years later, coadministration of the basic amino acids lysine and arginine was found to reduce the renal uptake of radiolabeled antibody fragments and somatostatin analogs (61,62). Behr et al reported that poly-L-lysine was more potent than L-lysine or D-lysine in reducing the renal retention of radiolabeled Fab9 fragments in rats, but poly-L-lysine was also more toxic.…”
Section: Reduction Of Renal Uptakementioning
confidence: 99%
“…It was recently shown that renal uptake of somatostatin analogues can be inhibited by maleic acid, which interferes with cellular energy supplies [10], by colchicine [11] due to dysfunction of proximal tubule reabsorption processes and by positively charged amino acids such as lysine and arginine [10,12,13]. Based on animal studies and clinical data [6,[14][15][16][17], PRRT is nowadays performed by coinfusion of lysine and arginine for kidney protection.…”
Section: Introductionmentioning
confidence: 99%